Expressionism in the Cinema - Brill, Olaf (Traditions in World Cinema Ser., 2017)
An innovative and wide-ranging collection, Expressionism in Cinema re-canonizes the classical Expressionist aesthetic, extending the critical and historical discussion beyond pre-existing scholarship into comparative and interdisciplinary areas of film research that reach across national boundaries.